"Calidad de la canal de los cerdos sacrificados en tres mataderos (Buena Fe, Quevedo y Valencia) de la Provincia de los Ríos 2019". - Macías Macías, Angie Tatiana (2020)
The present study was carried out to determine the quality of the carcass of pigs slaughtered in three slaughterhouses, the samples were taken in the municipal slaughterhouses of the cantons of Buena Fè, Quevedo and Valencia in the province of Los Ríos. To carry out this study, the investigative method was used, in addition, a completely randomized design was used with 3 treatments and 4 repetitions, the physical quality was evaluated; pH, cooking and dripping losses, backfat thickness. It was found that the slaughterhouse of the Quevedo canton offers good quality pig carcasses to the market, followed by the Valencia canton, the quality of its carcasses is within normal parameters. However, in the slaughterhouse of Buena Fè canton, it was found that PSD meats (pale exudative soft meats) of lower quality, a relatively low pH and high fat percentage were sold. Also, a checklist of questions was carried out to determine the general and hygienicsanitary conditions of the three litters under study, finding that the slaughterhouse of Buena Fe, like the slaughterhouse of Valencia, is in terrible sanitary and infrastructure conditions. Most of them comply with the standards established by the Slaughterhouse Law in the slaughter area and process. However, the Quevedo slaughterhouse has a good construction and design, most of it applies all established standards and complies with all slaughter processes. Keywords: quality, slaughterhouse, slaughter, sanitary conditions, standards